2016
DOI: 10.5935/1678-9741.20160076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early Outcomes with Three Approaches for Combined Coronary Revascularization and Carotid Endarterectomy

Abstract: ObjectiveThis study aims to compare three different surgical approaches for combined coronary and carotid artery stenosis as a single stage procedure and to assess effect of operative strategy on mortality and neurological complications.MethodsThis retrospective study involves 136 patients who had synchronous coronary artery revascularization and carotid endarterectomy in our institution, between January 2002 and December 2012. Patients were divided into 3 groups according to the surgical technique used. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
5
0
4
Order By: Relevance
“…A.A. Dönmez и соавт. [11] получили аналогичные результаты, отметив, что при одновременном КШ и КЭАЭ в условиях работающего сердца риски развития ОНМК, ОИМ и летальности не возрастают. Данные нашего исследования коррелируют с выводами работ [10,11].…”
Section: Discussionunclassified
“…A.A. Dönmez и соавт. [11] получили аналогичные результаты, отметив, что при одновременном КШ и КЭАЭ в условиях работающего сердца риски развития ОНМК, ОИМ и летальности не возрастают. Данные нашего исследования коррелируют с выводами работ [10,11].…”
Section: Discussionunclassified
“…Guibaud et al (40) also stated hypothermia below 28°C provides better cerebral protection especially for patients with bilateral carotid lesions. In contrast to this benefit, hypothermia during CEA had found to increase risk of MI (OR=3.5, CI=0.8-15.5) due to increased cross clamp and cardiopulmonary bypass times (37) .…”
Section: What Are the Surgical Options For Cea; Synchronous Or Stagedmentioning
confidence: 92%
“…In the literature, reported rate of mortality is between 0-4.5% and rate of stroke is between 0-3.1% for combined CEA and off-pump CABG (34)(35)(36)(37)(38)(39) . Eren et al (35) reported no stroke and 3.7% mortality for patients who had CEA and simultaneous off-pump CABG.…”
Section: What Are the Surgical Options For Cea; Synchronous Or Stagedmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach is the performance of carotid endarterectomy and CABG as a stepwise procedure, carotid endarterectomy, and CABG ("staged" procedure), with endarterectomy being performed prior to the establishment of extracorporeal circulation (18)(19)(20)(21). Most surgeons recommend this type of operative approach, especially for patients who have stable angina pectoris and who are hemodynamically stable (5).…”
Section: Introductionmentioning
confidence: 99%